Redox‐Neutral Synthesis of Polycyclic Azaheterocycles via Cobalt‐Catalyzed Hydroarylation/Annulation of Maleimides. Issue 21 (1st October 2022) - He, Yequan; Li, Wenwei; Zhou, Honggui; Zeng, Ge; Chen, Zhongyan; Ge, Jing‐Yuan; Lv, Ningning; Chen, Jiuxi
Abstract: Herein, we report a cobalt‐catalyzed hydroarylation of maleimides followed by an annulation sequence for the synthesis of polycyclic azaheterocycles in one pot. The reaction proceeds under redox‐neutral conditions and is compatible with various functional groups. Notably, the as‐prepared product exhibits potential photophysical properties. Abstract :